(untitled) (Research, Society and Development, 2023)
Class III malocclusion is considered one of the most complex, and may involve bone, tooth and musculature structure or a combination of these elements. A striking class III facial feature is the anterior crossbite. The objective of this work is to show the importance of early treatment of Angle class III malocclusion, through the presentation of a clinical case of a child patient, in the growth phase, treated with interceptive orthodontics with orthodontic and orthopedic effect on the progeny arch. The patient was treated in the Orthodontics specialization at the Facop / IBEN Advanced Graduate Unit – Manaus/AM. He was diagnosed with Angle class III malocclusion, presenting anterior crossbite. Treatment was performed with a modified SN3 appliance with an Echler arch and, later, with a progenic appliance, seeking transverse maxillary expansion, buccalization of the upper anterior battery and lingualization of the lower anterior battery. The treatment lasted one year and six months, with success in uncrossing the anterior crossbite. The appliances demonstrated good efficiency for the treatment of milder cases of class III malocclusion with anterior crossbite. They have a low cost, generate little discomfort in use, in addition to being easy to use and handle. The study demonstrated the importance of identifying, diagnosing and treating class III early, demonstrating clinical success in the planned interceptive and orthopedic treatment, avoiding aggravations, the need for future treatments and/or greater difficulties in subsequent interventions.